Changes in 15NO3- Availability and Transpiration Rate Are Associated With a Rapid Diurnal Adjustment of Anion Contents as Well as 15N and Water Fluxes Between the Roots and Shoots - Orieux, Charline; Demarest, Gilles; Decau, Marie-Laure; Beauclair, Patrick; Bataillé, Marie-Paule; Le Deunff, Erwan (Frontiers in Plant Science, 2018)
Background and aims: Understanding interactions between water and nitrate fluxes in response to nitrate availability and transpiration rate is crucial to select more efficient plants for the use of water and nitrate. Methods: Some of these interactions were investigated in intact Brassica napus plants by combining a non-destructive gravimetric device with 15NO3 labelling. The set-up allowed high-resolution measurement of the effects of a cross-combination of two concentrations of KNO3 or KCl (0.5 and 5 mM) with two different rates of transpiration controlled by the relative humidity during a day-night cycle. Key results: Results show that (1) high external nitrate concentrations increased root water uptake significantly whatever the transpiration rate, (2) nitrate translocation depended both on the rate of nitrate uptake and loading into xylem (3) dilution-concentration effect of nitrate in the xylem was mainly modulated by both external nitrate availability and transpiration rate, (4) dynamic changes in 15 14 N translocation in the xylem modified shoot growth and capacitance, and (5) variations in tissue concentrations of NO3induced by the experimental conditions were balanced by changes in concentrations of chloride and sulphate ions. These effects were even more amplified under low transpiration condition and 0.5 mM external nitrate concentration. Conclusions: Taken together, these results highlight the fine and rapid adjustment of anion contents, nitrate and water flows to changes in transpiration rate and nitrate availability during a day-night cycle. The use of this non-invasive gravimetric device is therefore a powerful tool to assess candidates genes involved in nitrogen and water use efficiency.